2022
DOI: 10.1155/2022/2226761
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heparin and Its Preparations on Disseminated Intravascular Coagulation Mortality and Hospitalization: A Systematic Review

Abstract: Background and Aim. Disseminated intravascular coagulation (DIC) is a critical clinical condition that is expressed by systemic activation of the homeostatic system, leading to elevation of thrombin deposition and result in microvascular thrombi. Heparin makes a good effect on hypercoagulability states through inhibition of thrombin. The present study aimed to summarize and discuss the results of randomized clinical trials and cohort studies regarding the effect of heparin and its preparations on DIC mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Following these studies, Omidkhoda et al 23 performed a meta-analysis of the six RCTs and two cohort studies that examined heparins' effects on DIC from various underlying diseases. Although reduced mortality by UFH or LMWH was reported, five studies targeted or included sepsis cases, and heparins were used as the control of the study drugs in four studies.…”
Section: Effectiveness Of Heparins On Sepsis-associated Dicmentioning
confidence: 99%
“…Following these studies, Omidkhoda et al 23 performed a meta-analysis of the six RCTs and two cohort studies that examined heparins' effects on DIC from various underlying diseases. Although reduced mortality by UFH or LMWH was reported, five studies targeted or included sepsis cases, and heparins were used as the control of the study drugs in four studies.…”
Section: Effectiveness Of Heparins On Sepsis-associated Dicmentioning
confidence: 99%
“…However, little evidence supports the efficacy of anticoagulant therapy in addition to antibiotics and source control. Despite studies of several anticoagulants in large-scale randomized controlled trials (RCTs), no current anticoagulant has yet demonstrated efficacy [ 61 , 63 ]. Potential reasons include the variability of clinical presentation in sepsis [ 61 ], but as previously described, anticoagulant therapy should be considered only for patients with a coagulation disorder, as best noted the optimal target is sepsis-associated DIC with high disease severity [ 38 , 39 ] (Fig.…”
Section: How Should We Treat Sepsis-associated Dic?mentioning
confidence: 99%
“…However, the study population was not restricted to patients with coagulopathy/DIC. Another systematic review of heparin in DIC [ 63 ] was limited by including studies in which three out of eight studies used heparin as the control. Although heparin is strongly recommended for COVID-19 [ 64 ], its efficacy for sepsis-associated DIC is still unclear.…”
Section: How Should We Treat Sepsis-associated Dic?mentioning
confidence: 99%
“…Although several studies have addressed the association between coagulation parameters and disease severity in the acute phase of COVID-19, data on the relationship of these parameters to long-term outcome are scarcer. Moreover, while the effects of various anticoagulants have been reported in several studies [ 13 , 14 ], the impact of antiviral agents on these variables is not known.…”
Section: Introductionmentioning
confidence: 99%